ANALISIS PENGELOLAAN DANA DESA DI DESA TIREM KECAMATAN LEBAK WANGI KABUPATEN SERANG ANALYSIS OF VILLAGE FINANCIAL MANAGEMENT IN TIREM VILLAGE, LEBAK WANGI SUB DISTRICT, SERANG REGENCY - Rahmawati Rahmawati; Ipah Ema Jumiati; Deden Muhammad Harist (Universitas Sultan Ageng Tirtayasa, 2017)
The mandate of Village Law No.6 of 2014 that Village has an allocation of Village Fund (ADD) at least 10% of balancing funds received by Regency/City in Regional Budget In addition, the village also get the allocation of funds from the state budget, the allocation of the budget is directed to the village determined 10% (Ten percent) from and beyond the On Top Transfers gradually. As a consequence of the receipt of these funds, it is necessary to understand the importance of village administration to the management of village finances in accordance with prevailing laws and regulations with village financial management principles such as participation, accountability, transparency and budget discipline. Tirem Village is one of the villages that get the village funds in 2014 amounting to Eight Hundred Million Rupiah (Rp 800.000.000,00). The crucial problem faced by the village government is how to manage the large village funds effectively, efficiently and accountably. Village financial management is a cycle consisting of planning, budgeting, implementation, administration, reporting and accountability. The research method used descriptive with qualitative approach. The research informants are village apparatus, BPD, community leaders, religious leaders, and the people of Tirem village. The results show that the financial management of village funds is still not optimal. Most of them are used for physical/ infrastructure development such as rehabilitation of village office buildings that are not feasible and the construction of village roads that are still in the form of land. In terms of village financial reports, village apparatuses, especially financial treasurers, have difficulty in making accountability reports and concerns about errors in budget usage. In the oversight function, the use of village funds is monitored and recognized by Village Consultative Bodies and the community. The village apparatus is experiencing difficulties in understanding the rules of taxation so as not to know the expenditure component which contains the elements of tax and procurement activities of goods and services, especially the infrastructure that uses the auction system. Recommendation is running technical guidance activity of financial accountability report preparation that must be done by local government.